Trust in physicians among patients with head and neck cancer before and after treatment. Issue 9 (26th April 2021) - Highland, Julie; Aylward, Alana; Do, Olivia; Monroe, Marcus; Buchmann, Luke
Abstract: Background: Little is known about physician trust in patients with head and neck cancer. This study's aim is to evaluate trust pre‐ and post‐treatment. Methods: A study was conducted of 50 patients with head and neck cancer at a tertiary referral center. Surveys administered before and after treatment included several validated survey tools including the Trust in Oncologist Scale Short Form. Results: There was an increase in overall trust scores ( p  < 0.001). Female patients ( p  = 0.034) and those who received chemotherapy ( p  = 0.001) were less trusting post‐treatment. Patients with more comorbidities ( p  = 0.045) and progression of disease ( p  = 0.029) had higher final trust than those without. Patients with high initial distress scores showed a decrease in trust ( p  = 0.023). Conclusions: Patients with head and neck cancer trust their surgeon more after completion of treatment, with specific characteristics having a variable impact on trust scores.